Manajemen risiko dalam praktek keuangan syariah: Studi kasus di Baitul Maal waat Tamwil - Nurjihan, Mumtazah (Maliki Interdisciplinary Journal, 2024)
Since every decision carries a level of risk, risk management is crucial to achieving goals. There are two kinds of risks. The first one belongs to a particular project or bank, and the second one has a domino effect that can affect many projects, industries, or even states. The latter is systemic risk, which makes diversification difficult. Because of the unique risk associated with Islamic principles, Islamic banking risk management differs from conventional banking. Identifying, evaluating, predicting, and monitoring risks are all parts of this process. To manage risk, transparency in providing information about business and bank products is crucial. Banks can use a variety of risk assessment approaches, but the Basel II standard calculates capital requirements based on the bank’s risk profile. In the case of Islamic banks, the implementation of risk management must be consistent with the objectives, policies, size, and complexity of the organization. In addition, a case study was conducted on UGT Sidogiri’s risk management strategy, which includes identification, categorization, monitoring, and risk evaluation. Overall, banking success depends on effective risk management; there are many ways to manage and mitigate risk.